1986
DOI: 10.5479/si.00810282.430
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Psilopinae (Diptera: Ephydridae), I: A Revision of the Shore Fly Genus Placopsidella Kertacsz

Abstract: SERIES PUBLICATIONS OF THE SMITHSONIAN INSTITUTION Emphasis upon publication as a means of "diffusing knowledge" was expressed by the first Secretary of the Smithsonian. In his formal plan for the Institution, Joseph Henry outlined a program that included the following statement: "It is proposed to publish a series of reports, giving an account of the new discoveries in science, and of the changes made from year to year in all branches of knowledge." This theme of basic research has been adhered to through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 3 publications
(3 reference statements)
0
45
0
Order By: Relevance
“…The descriptive terminology, with the exceptions noted in Mathis (1986) and Mathis and Zatwarnicki (1990a) and below, follows that published in McAlpine (1981). Specimens of Axysta are moderately small, and study and illustration of the male genitalia required use of a compound microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive terminology, with the exceptions noted in Mathis (1986) and Mathis and Zatwarnicki (1990a) and below, follows that published in McAlpine (1981). Specimens of Axysta are moderately small, and study and illustration of the male genitalia required use of a compound microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens of Axysta are moderately small, and study and illustration of the male genitalia required use of a compound microscope. We have followed the terminology for most structures of the male genitalia that other workers in Ephydridae have used (see references in Mathis 1986;Mathis and Zatwarnicki 1990a, 1990b, Zatwarnicki 1996 except the term aedeagal apodeme has been replaced with the synonymous term phallapodeme.…”
Section: Methodsmentioning
confidence: 99%
“…The descriptive terminology, with the exceptions noted in MATHIS (1986) and MATHIS & ZATWARNICKI (1990a), follows that published in the 'Manual of Nearctic Diptera' (MCALPINE 1981). Because specimens of Parydrini are generally moderately small, usually less than 4.0 mm in length, study and illustration of the male terminalia required use of a compound microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Because specimens of Parydrini are generally moderately small, usually less than 4.0 mm in length, study and illustration of the male terminalia required use of a compound microscope. We have followed the terminology for most structures of the male terminalia that other workers in Ephydridae have used (see references in MATHIS 1986, MATHIS & ZATWARNICKI 1990a, such as surstylus. ZATWARNICKI (1996) suggested that the preand postsurstylus correspond with the pre-and postgonostylus and that the subepandrial plate is the same as the medandrium.…”
Section: Methodsmentioning
confidence: 99%
“…The terminology, with the exceptions noted in Mathis (1986) and Mathis & ZatWarnicki (1990a, 1990b, follows Mcalpine (1981). ZatWarnicki (1996) suggested that the pre-and postsurstylus correspond with the pre-and postgonostylus and that the subepandrial sclerite is the same as the medandrium.…”
Section: Methodsmentioning
confidence: 99%